The Validity of the MSI-BPD Among Inpatient Adolescents. (April 2014) - Noblin, J. Leigh; Venta, Amanda; Sharp, Carla
Although the McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD) has shown validity in adult samples, only one study has explored its validity in adolescents and, to our knowledge, the measure has not been validated with inpatient adolescents. The aim of the current study was to evaluate the reliability, and convergent and criterion validity, of the MSI-BPD in an effort to establish the clinical utility of the MSI-PBD as a screening measure for BPD in inpatient adolescents. A total of 121 adolescents from an acute care inpatient unit were recruited for the study. Convergent validity was examined with established measures of BPD in adolescents, including the use of receiver operating characteristics analyses to establish a clinical cutoff score for the MSI-BPD in predicting a diagnosis of BPD. Criterion validity was examined by using this clinical cutoff to investigate group differences in suicidal ideation and Axis I symptoms, known correlates of BPD. Findings demonstrated support for validity of the MSI-BPD when used among inpatient adolescents, and established a clinical cutoff of 5.5. Taken together, this study demonstrates adequate validity for the MSI-BPD, and suggests it is a valuable screening measure for BPD in adolescent inpatients.